1996
DOI: 10.1111/j.1432-1033.1996.0104h.x
|View full text |Cite
|
Sign up to set email alerts
|

Three α‐Galactosidase Genes of Trichoderma reesei Cloned by Expression in Yeast

Abstract: Three cx-galactosidase genes, agll, ag12 and ag13, were isolated from a cDNA expression library of Trichoderma reesei RutC-30 constructed in the yeast Saccharomyces cerevisiae by screening the library on plates containing the substrate 5-bromo-4-chloro-3-indolyl-a-D-gnlactopyranoside. The genes ugll, ag12 and agl3 encode 444, 746 and 624 amino acids, respectively, including the signal sequences. The deduced amino acid sequences of AGLI and AGLIII showed similarity with the a-galactosidases of plant, animal, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 47 publications
2
73
0
Order By: Relevance
“…However, one possible member of GH54, ␣-L-arabino- furanosidase from H. jecorina PC-3-7 (HjPCAbf), is reported to contain a non-catalytic xylan-binding domain in its C-terminal 18-kDa portion, which can be proteolytically cleaved by pepsin (37). HjPCAbf is probably a member of GH54 because its Nterminal amino acid sequence is almost identical to that of GH54 ␣-L-arabinofuranosidase/␤-xylosidase from H. jecorina RutC-30 (HjRuAbf) (38). Therefore, the xylan-binding domain of HjPCAbf seems to correspond to the ABD of AkAbfB.…”
Section: Resultsmentioning
confidence: 99%
“…However, one possible member of GH54, ␣-L-arabino- furanosidase from H. jecorina PC-3-7 (HjPCAbf), is reported to contain a non-catalytic xylan-binding domain in its C-terminal 18-kDa portion, which can be proteolytically cleaved by pepsin (37). HjPCAbf is probably a member of GH54 because its Nterminal amino acid sequence is almost identical to that of GH54 ␣-L-arabinofuranosidase/␤-xylosidase from H. jecorina RutC-30 (HjRuAbf) (38). Therefore, the xylan-binding domain of HjPCAbf seems to correspond to the ABD of AkAbfB.…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent work with ␣-galactosidases has indicated that these enzymes fill an essential role in the breakdown of side chains from large oligosaccharides such as hemicellulose and soy (10,16). These enzymes are intracellular and are induced after breakdown of the target substrate's polymer backbone by extracellular enzymes such as ␤-mannanase (18). Both ␣-and ␤-linkages are common in the side chains of sugar polymers produced by plants and in the complex saccharides adsorbed to humic acid substances in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enzymes with cellulolytic activity, a number of enzymes have been identified in T. reesei that degrade hemicellulose (17,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). These enzymes include four xylanases (Xyn1, Xyn2, Xyn3, and Xyn4) and mannanase (Man1), which cleave the xylan and mannan main chains of hemicellulose.…”
mentioning
confidence: 99%